Drug resistance profile among multi-drug resistant tuberculosis patients at diagnosis and correlation with history of anti-tubercular treatment in a tertiary care center - Kumar, Rahul; Garg, Rajiv; Kshetrimayum, Silpa; Jain, Amita (International Journal of Advances in Medicine, 2019)
Background: Drug Resistant Tuberculosis (DR-TB) is a major threat to the realization of the goal of a TB free world in the near future. It is important to study the reasons for the increasing number of such cases so that effective action can be taken to control this growing epidemic. Methods: Sputum from 36 patients diagnosed with acquired pulmonary Multidrug Resistant Tuberculosis (MDR-TB) were subjected to first- and second-line Drug Sensitivity Testing (DST) after liquid culture in mycobacterium growth Indicator Tube (MGIT). Primary MDR-TB cases were excluded. The relation of the drug sensitivity profile with the history of prior treatment taken was statistically analysed. Results: Majority of the patients had received appropriate treatment, and most had adhered to prescribed treatment. Among the 36 patients, 24(66.7%) were found to be Pre-Extensively Drug Resistant (Pre-XDR-TB) and 4(11.1%) were extensively drug resistant XDR-TB cases. Inappropriate prescription of fluoroquinolone (FQ) was found to be most common. Prior intake of any drug was not found to significantly affect subsequent resistance to that drug. Conclusions: Fluoroquinolone resistance is quite common in patients with DR-TB (66.7%). This study did not find the prior use of FQ or any other drug to significantly affect subsequent resistance to the drug. Primary drug resistance is thus a major concern. 11.1% patients were found to be XDR-TB cases. Hence DST for first- and second-line drugs should be done at the time of diagnosis to avoid failure of treatment with a predesigned regimen.